Republic of Armenia Programmatic Fiscal Work : Supporting Effective Fiscal Management - World Bank (World Bank, Washington, DC, 2016)
The objective of this report, which is the third in a series of programmatic public expenditure reviews (PPER), is to identify potential measures to strengthen public finances in line with the Government’s strategy to reduce fiscal risks and support budgetary consolidation. The PPER series assesses public expenditures and their alignment with development goals. For this phase of the PPER, three areas were identified with the Government as absent from previous reports yet of particular relevance given growing spending pressures. The first is efficiency of government spending on social sectors and public investment, where efficiency is defined in terms of outcomes achieved. The second area of relevance encompasses quasi-fiscal risks and contingent liabilities of the energy sector. The third area pertains to selected subsidies, which are budgeted to rise exponentially in 2016. This report is anchored in the Country Partnership Strategy (CPS) pillars of improving governance, efficiency of public administration, and service delivery. This report is divided into three chapters, each covering the very distinct fields of fiscal management identified above: (i) first chapter covers on Macroeconomic and Fiscal Challenges; (ii) second chapter focuses on Quasi-Fiscal Pressures of the Energy Sector; and (iii) third chapter deals with the Assessment of Explicit Budget Subsidies. The report employs highly discrete conceptual and analytic frameworks for each of the analyzed areas in order to draw conclusions and provide recommendations.